2009
DOI: 10.1093/bja/aep173
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of economical aspects of interscalene brachial plexus blockade and general anaesthesia for arthroscopic shoulder surgery

Abstract: Ultrasonographic-guided ISB is a cost-effective method for arthroscopic shoulder surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 12 publications
6
65
1
4
Order By: Relevance
“…Another perceived barrier may be the longer time required to perform a femoral nerve block, as compared to traditional methods of pain management. However, two published studies 30,31 found that nerve blocks increased efficiency by reducing the total operation time, as well as the incidence of readmission due to pain. In order to effectively implement femoral nerve blocks into routine ED care, the barriers to use need to be explored further, and then implementation interventions that specifically address these identified barriers need to be developed and evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Another perceived barrier may be the longer time required to perform a femoral nerve block, as compared to traditional methods of pain management. However, two published studies 30,31 found that nerve blocks increased efficiency by reducing the total operation time, as well as the incidence of readmission due to pain. In order to effectively implement femoral nerve blocks into routine ED care, the barriers to use need to be explored further, and then implementation interventions that specifically address these identified barriers need to be developed and evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there was no difference between the groups in terms of surgeon satisfaction. In the study conducted by Gonano et al (10), hemodynamic instability was observed more in patients who underwent general anaesthesia compared to those who underwent brachial plexus blockage. In our study as well, in accordance with the literature, hemodynamic findings of BPB Group patients were more stable than general anaesthesia group patients.…”
Section: Discussionmentioning
confidence: 90%
“…In our study, there were three patients in the general anaesthesia group who had postoperative nausea and vomiting, while there weren't any in the regional anaesthesia group. In the study conducted by Gonano et al (10), it was claimed that among the patients who would have shoulder arthroscopy, regional anaesthesia patients were more cost effective than general anaesthesia patients. It was shown that regional anaesthesia patients considerably reduced medicine consumption, anaesthesia control duration, and the stay duration in PACU.…”
Section: Discussionmentioning
confidence: 99%
“…First, the use of a dedicated regional anesthesia block area facilitates early placement of BPB and allows sufficient time to ensure surgical anesthesia before the incision is performed, which likely contributed significantly to the high block success rate. When regional anesthesia with a dedicated block area is compared with GA, previous research has shown that regional anesthesia decreases anesthesia-controlled time (traditionally defined as the interval between surgical closure and OR exit of one patient plus the interval between the next patient entering the OR and being ''anesthesia ready'') for upper extremity surgery, 12,14,20 although the time saved was small (from 4 to 11 min). However, it is important to point out that Local anesthesia only n = 5 Bier block n = 2 Median nerve block n = 2 General anesthesia (regional anesthesia not attempted) n = 31 General anesthesia plus regional anesthesia n = 28 Cases that could not be matched n = 4* Age < 18 n = 2 Brachial plexus block as intended primary anesthetic modality (n = 133) † Supraclavicular block n = 88 Infraclavicular block n = 37 Brachial plexus block not otherwise specified n = 6 Infraclavicular catheter n = 1 Supraclavicular catheter n = 1 An attempt was made to match surgical procedures as closely as possible (i.e., same anatomic location and same operation).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in upper extremity surgery, use of brachial plexus blockade (BPB) rather than general anesthesia (GA) leads to reduced postoperative pain and analgesic requirements, [5][6][7][8][9][10][11][12][13] decreased postoperative nausea and vomiting (PONV), [5][6][7][8][9]13 and reduced length of stay in the postanesthesia care unit (PACU). [6][7][8][9][10][11][12][13][14] The recent introduction of ultrasound technology has led to an increased interest in regional anesthesia as its use is associated with numerous advantages, including the potential for accelerated onset times and greatly improved success rates. [15][16][17] These attributes render ultrasound-guided regional anesthesia an attractive component of perioperative care models targeted to increase efficiency and throughput.…”
Section: Résumémentioning
confidence: 99%